IMPLEMENTASI PENYIMPANAN BAHAN MAKANAN DI FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Muhadi, Ihsan; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
This research was motivated from the observation regarding the storage of foodstuffs at the Faculty of Tourism and Hospitality, there is no longer space available to received the foodstuffs, unorganized materials of perishabel and grouceries. This research was consisted by two indicators of Materials Perishabel and Materials grouceries. This research was descriptive research with qualitative data. The sampling technique was done by purposive sampling. Data were collected by observation, interview and documentation involving informans and respondents. According to the research, it was revealed that (1) Perishable materials; storage according the temperature was done as needed, Perishable materials, that were available are cheddar cheese, mozzarella cheese, korsvet, sausage, cream, butter, with as a refrigerator storage equipment in the temperature of 18-20 Â°C. mean while the storage technique of perishable is using first in first out system. For the cleanliness of storage equipments cleaning was done twice a week. (2) Groceries materials; storage of groceries materials carried by differentiating according to the type made at the time of food receiving, Groceries materials available were flour, sugar, powdered sugar, dried herbs, edible oils, chocolate powder, gelatin powder and fermifan with made of wood with two shelves as a storage equipmen, The storage technique of groceries is also using the first in first out system. Then the positioning of groceries stock card whice incorrect has become the problem for students to found the availability of groceries, and for the cleanliness of storage equipments cleaning was done three times in a semester.Keywords: Materials Perishabel and Materials grouceries, First in first out.